Diagnostic value of D-dimer to fibrinogen ratio for pulmonary embolism in postpartum women - Zhou, Wenting; Qu, Cuicui; Liu, Xiaohua; Huang, Junfeng (BMC pregnancy and childbirth, 2024)
Pulmonary embolism is a common disease associated with high mortality and morbidity. Diagnosing pulmonary embolism is challenging due to diverse clinical presentations and the lack of specific biomarkers. The study aimed to investigate the diagnostic value on pulmonary embolism for postpartum women by D-dimer to fibrinogen ratio, and it combined with neutrophil-to-lymphocyte ratio or platelet-to-lymphocyte ratio. A total of 537 women with suspected pulmonary embolism were selected as the research subjects from the Shanghai First Maternity and Infant Hospital between 1 January 2019 and 31 October 2022. The D-dimer to fibrinogen ratio and it combined with neutrophil-to-lymphocyte ratio or platelet-to-lymphocyte ratio were applied to evaluate the clinical probability of pulmonary embolism, and the positive predictive value of both scores were calculated using computed tomography pulmonary arteriography as a gold standard. The diagnostic value of D-dimer to fibrinogen ratio, combined with neutrophil-to-lymphocyte ratio or platelet-to-lymphocyte ratio was evaluated by the area under the curve, sensitivity, specificity, and other indicators in the receiver operator characteristic curve. Among the 502 women included for analysis, 194 (38.65%) were definitely diagnosed as pulmonary embolism. The positive predictive values of D-dimer to fibrinogen ratio and it combined with platelet-to-lymphocyte ratio or neutrophil-to-lymphocyte ratio were 70.1%, 50.5%, and 56.5%, respectively in the postpartum women, the area under the curve for the D-dimer to fibrinogen ratio and it combined with platelet-to-lymphocyte ratio or neutrophil-to-lymphocyte ratio were 0.606 (95%CI: 0.562-0.650), 0.624 (95%CI: 0.575-0.673), and 0.639 (95%CI: 0.592-0.686), respectively. The negative predictive values of D-dimer to fibrinogen ratio, it combined with platelet-to-lymphocyte ratio or neutrophil-to-lymphocyte ratio were 50.5%, 70.1%, and 69.8%, respectively. The diagnostic value of the D-dimer to fibrinogen ratio was higher than the D-dimer for the postpartum women with suspected pulmonary embolism. The combination of either the neutrophil-to-lymphocyte ratio or the platelet-to-lymphocyte ratio with D-dimer to fibrinogen ratio is an appropriate strategy to rule out pulmonary embolism.